The Influence Of Differentiation On Customer Satisfaction Of Toyota Car Avanza Users at PT. Hadji Kalla Alauddin Branch Makassar City - Bahar, St Sarah Ramadhani; Muh. Nur Yamin; Risma Niswaty; Andi Mahdiana Mardatillah (Business Research and Administration Innovation, 2024)
This study aims to find out how the influence of Market Orientation and Product Innovation on Marketing Performance in Micro Trade Business in South Sulawesi. The type of research is quantitative with data collection techniques were carried out by document and questionnaires. The population in this research are micro business actors in the trade who registered at Dinas Koperasi dan UKM Provinsi Sulawesi Selatan, amounting to 244.592. The sampling method used is Slovin with an error rate of 10%, which is obtained 100 respondents. The data obtained from the research results were processed using the SPSS version 25 application which consisted of validity and reliabilition tests to test the research instrumen as well as descriptive data analysis tests and inferential statistical analysis to test existing hypotheses. The results showed that market orientation was in the very good category, product innovation was in the good category, and marketing performance was in the very good category. The results of inferential analysis show that there is a significant influence between market orientation and product innovation on the marketing performance of micro trade business in South Sulawesi